BIOLOGICAL RULE OF SHORT ROTATION Populus nigra PLANTATION IN ENVIRONMENTAL EQUILIBRIUM. - Mohammed, Ammar Jasim (Diyala Agricultural Sciences Journal, 2016)
This study has been conducted of irrigated Populus nigra plantation in Warso village – Zakho – Governorate of Dohuk at the Northern part of Iraq . The aims were to determine the dry weights biomass for different tree and stand parameters above ground surface ; in order to gain a clear view on carbon stock retainer for different tree for different tree parts. The basic data of this study were collected from the stands according to the Stratified Random Sampling through felling of 27 poplar trees whose parts , above ground surface , were weighted in addition to sub samples from each whole tree parameters in order to prepare estimating dry weights . By using the data and different available regression methods within Statgraphics program system , it become possible to prepare different tree parameters biomass forecasting equations . These equations were tested according to different precision measures ; Adjusted Determination Coefficient , Standard Error , Ohtomo test , Furnival index and Residual Analysis Test. Access at best equation to estimating carbon stock retainer .